Native-immigrant gaps in educational and school-to-work transitions in the second generation: The role of gender and ethnicity - Stijn Baert; Frank Heiland; Sanders Korenman (Institute for the Study of Labor (IZA), 2014)
We study how native-immigrant (second generation) differences in educational trajectories and school-to-work transitions vary by gender. Using longitudinal Belgian data and adjusting for family background and educational sorting, we find that both male and female second-generation immigrants, especially Turks and Moroccans, lag natives in finishing secondary education and beginning tertiary education when schooling delay is taken into account, though the female gap is larger. The same is true for residual gaps in the transition to work: native males are 30% more likely than comparable Turkish males to be employed three months after leaving school, while the corresponding female gap is 60%. In addition, we study demographic behaviors (fertility, marriage and cohabitation) related to hypotheses that attribute educational and economic gaps to cultural differences between immigrants and natives.
Keywords: I24; J15; J16; J70; Z10; C35; 330; educational attainment; school-to-work transitions; dynamic selection bias; ethnic minorities; gender differentials; economic sociology